2019
DOI: 10.1088/1757-899x/544/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Key Structures of RV Reducer Based on Finite Element Method

Abstract: In this paper, key structures of the RV reducer were calculated by finite element method respectively, including the stress and deformation of cycloidal-pin wheel and eccentric shaft. The results show that the contact stress and equivalent stress of cycloidal-pin wheel and eccentric shaft are far less than the strength of materials. It means the strength is not the main consideration of design and manufacture. The stiffness of eccentric shaft is less than the cycloidal-pin wheel, which had a great influence on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…To validate the robustness of our model, the predictions are critically assessed using a suite of error metrics, providing a holistic view of its performance and reliability. The optimized model is shown in Equation (17).…”
Section: Bayesian-enhanced Least Squares Genetic Algorithm Optimizati...mentioning
confidence: 99%
See 1 more Smart Citation
“…To validate the robustness of our model, the predictions are critically assessed using a suite of error metrics, providing a holistic view of its performance and reliability. The optimized model is shown in Equation (17).…”
Section: Bayesian-enhanced Least Squares Genetic Algorithm Optimizati...mentioning
confidence: 99%
“…Sun and Han's examination of the China Bearing Reducer (CBR) underscored the significance of the clearance between the cycloid teeth and pin on the contact force and stress [16]. Using finite element methods, Song et al found that in RV reducers, the eccentric shaft's stiffness is of greater concern than the material strength [17]. Hsieh and team compared traditional and novel designs for two-stage speed reducers, analyzing their implications for stress and motion [18].…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have conducted research on the transmission errors and contact conditions of cycloid gears. Lei et al [18] carried out finite element analysis on RV reducers and Spinea reducers in an attempt to reveal the static characteristics due to the different structures. Yu et al [19] used a non-Hertzian elastic contact method to establish an equation based on the elastic deformation of the gear teeth and the flexibility of the load distribution to calculate the load distribution of the tooth profile more accurately.…”
Section: Introductionmentioning
confidence: 99%